The Relationship between Completeness of Inpatient Claims and BPJS Health Claim Approval at UPT RSUD Massenrempulu Enrekang: Hubungan Kelengkapan Klaim Rawat Inap Dengan Persetujuan Klaim BPJS Kesehatan Di UPT RSUD Massenrempulu Enrekang - Sinar, Sinar; Manggandhi, Yuyun; Kusumawati, Erna Adita (Universitas Muhammadiyah Sidoarjo, 2025)
The Massenrempulu Enrekang Regional Hospital technical Implementation Unit is a class C hospital where the hospital has outpatient and inpatient services as well as an emergency room. Based on the preliminary survey, it was found that there were incomplete medical records and incomplete claims administration requirements. this will affect the BPJS Health claim approval process. the aim of the research is to determine the relationship between the completeness of inpatient claims and the approval of BPJS Health claims. this research uses the Observational Analytical method with a cross sectional approach. the sample for this study was 80 medical records and BPJS Health inpatient claim files. The research instrument uses observation and interview guidelines. The research results show that there is a relationship between claim completeness (medical records and claim administration requirements) with BPJS Health claim approval. this is shown by the results of the Fisher Exactt test where the p value is: 0.002 (<0.05). the conclusion of this research is that there is a relationship between claim completeness and BPJS Health claim approval.